Les formations à genévriers rampants du Djurdjura (Algérie). Leur signification ecologique, dynamique et syntaxinomique dans une approche globale des cédraies kabyles - Quèzel, Pierre; Barbero, Marcel (Lazaroa, 1989)
The authors propose a new phyiosociologic interpretation of Juniperas comniunis subsp. hemisphaerica and Juniperus sabina shrublands in the Djurdjura. They make up two new associations: the Cynosuro balansae-Juniperetun, hemisphaericae and the Daphno oleoidis-Juniperetum sabinae, belonging to the new alliance Lonicero kabylicae-Juniperion hemisphaericae included in the order Querco Cedretalia atlanticae. The ecologic and biogeograpbic value of these communities is analized in a Westem-mediterrancan context as well as their dynamic importance. On this mountain, they correspond to ihe preforested level of cedar forests. For this reason, an attempt to inlerprel Kabylian cedar forests as a whole was made they belong to the new association Senecio perralderlani-Cedretum atlanticae. A diachronic evaluation of changes in native plant communities over a 30 year period is made, in particular as related to the creation of several local structures to protect natural resources.